2012
DOI: 10.1158/1078-0432.ccr-12-0392
|View full text |Cite
|
Sign up to set email alerts
|

Activation of HER Family Signaling as a Mechanism of Acquired Resistance to ALK Inhibitors in EML4-ALK–Positive Non–Small Cell Lung Cancer

Abstract: Purpose: Anaplastic lymphoma kinase (ALK) tyrosine kinase inhibitors (TKI) such as crizotinib show marked efficacy in patients with non-small cell lung cancer positive for the echinoderm microtubuleassociated protein-like 4 (EML4)-ALK fusion protein. However, acquired resistance to these agents has already been described in treated patients, and the mechanisms of such resistance remain largely unknown.Experimental Design: We established lines of EML4-ALK-positive H3122 lung cancer cells that are resistant to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
101
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(110 citation statements)
references
References 19 publications
5
101
1
1
Order By: Relevance
“…These mutations either involve the 'gatekeeper' residue (L1196) or sites at a distance from crizotinib binding (F1174L and C1156Y) (56,57). Other mechanisms, such as the activation of HER family signalling, have been demonstrated as ALK-TKI-resistant (58). The cytotoxic activity of crizotinib has also been demonstrated against tumours carrying the ROS1 rearrangement (4,59) and MET amplification (5).…”
Section: Clinically-relevant Target Drugsmentioning
confidence: 99%
“…These mutations either involve the 'gatekeeper' residue (L1196) or sites at a distance from crizotinib binding (F1174L and C1156Y) (56,57). Other mechanisms, such as the activation of HER family signalling, have been demonstrated as ALK-TKI-resistant (58). The cytotoxic activity of crizotinib has also been demonstrated against tumours carrying the ROS1 rearrangement (4,59) and MET amplification (5).…”
Section: Clinically-relevant Target Drugsmentioning
confidence: 99%
“…Bypass signaling, by v-Kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog (KIT) or EGFR, has also been described as a mechanism of resistance to crizotinib in ALK positive NSCLC 51 . EGF-induced activation of EGFR, HER2, and HER3, as well as a reduced level of ALK activation, was associated with sustained downstream signaling in the presence of ALK inhibitors, indicative of a shift in survival dependency from the ALK signaling pathway to HER family pathways in ALK-TKI-resistant cells 56 . .…”
mentioning
confidence: 94%
“…Numerous examples of bypass signaling activation have been discovered. For example, gene expression profiling of crizotinib-resistant versus crizotinibnaive NSCLC tumor samples identified EGFR and HER2 signatures as two of the most enriched gene expression signatures in resistant tumors (51,56,57). In one study, increased EGFR activation was identified in 4 of 9 cases (44.4%) when biopsy samples prior to crizotinib initiation and after development of resistance were compared (51).…”
Section: Anaplastic Lymphoma Kinase (Alk)mentioning
confidence: 99%